Effect Of Education Media Video On Improve Stroke Prevention Behavior In Continued Age In Wiyurejo Pujon Malang - Muslihati, Indun; Lisandy, Yonas Galang; Kasanah, Ririn; Winarko, Hendry Agustina (Journal Of Nursing Practice, 2018)
Background: Stroke is a disease caused by one of the pathological processes that affect the blood vessels of the brain. Efforts to reduce mortality from stroke can be done by health education about stroke disease. Purpose : The purpose of this research is to know the Influence of Media Video Education on the Enhancement of Prevention of Stroke in Elderly in Wiyurejo Village, Pujon Sub-district, Malang Regency. Methods : Pre-experimental design research design with one group pre-post test design. Population of all elderly (elderly) between 60-74 years in the Village Wiyurejo District Pujon Malang regency a number of 34 people. The sampling technique used was accidental sampling so that the sample was 32 people. Data analysis Using wilcoxon. Result : The results showed that stroke prevention behavior before giving video media almost half of educational (46,9%) respondents have bad behavior. After being given an educational video media showed almost half of them with sufficient behavior (43.8%). Conclusion : There is Influence of Educational Video Media to Improving Prevention Behavior of Stroke at Elderly in Wiyurejo Village, Pujon Sub-district, Malang Regency. Looking at the results of the study suggested that the provision of counseling about stroke prevention can be carried out repeatedly in the elderly so as to make efforts in preventing early